Substitution Method
The Substitution Method Consists of two main steps:
- Guess the Solution.
- Use the mathematical induction to find the boundary condition and shows that the guess is correct.
For Example1 Solve the equation by Substitution Method.
T (n) = T + n
We have to show that it is asymptotically bound by O (log n).
Solution:
For T (n) = O (log n)
We have to show that for some constant c
Put this in given Recurrence Equation.
T (n) ≤c log+ 1
≤c log+ 1 = c logn-clog2 2+1
≤c logn for c≥1
Thus T (n) =O logn.
Example2 Consider the Recurrence
T (n) = 2T+ n n>1
Find an Asymptotic bound on T.
Solution:
We guess the solution is O (n (logn)).Thus for constant 'c'.
T (n) ≤c n logn
Put this in given Recurrence Equation.
Now,
T (n) ≤2clog +n
≤cnlogn-cnlog2+n
=cn logn-n (clog2-1)
≤cn logn for (c≥1)
Thus T (n) = O (n logn).
2. Iteration Methods
It means to expand the recurrence and express it as a summation of terms of n and initial condition.
Example1: Consider the Recurrence
Solution:
T (n) = 2T (n-1) = 2[2T (n-2)] = 22T (n-2) = 4[2T (n-3)] = 23T (n-3) = 8[2T (n-4)] = 24T (n-4) (Eq.1) Repeat the procedure for i times T (n) = 2i T (n-i) Put n-i=1 or i= n-1 in (Eq.1) T (n) = 2n-1 T (1) = 2n-1 .1 {T (1) =1 .....given} = 2n-1
Example2: Consider the Recurrence
Solution:
T (n) = T (n-1) +1 = (T (n-2) +1) +1 = (T (n-3) +1) +1+1 = T (n-4) +4 = T (n-5) +1+4 = T (n-5) +5= T (n-k) + k Where k = n-1 T (n-k) = T (1) = θ (1) T (n) = θ (1) + (n-1) = 1+n-1=n= θ (n).
Comments
Post a Comment